Thirty-day outcomes of direct carotid artery stenting with cerebral protection in high-risk patients - Veselka, Josef; Cerná, Daniela; Zimolová, Petra; Blasko, Peter; Fiedler, Jirí; Hájek, Petr; Maly, Martin; Zemánek, David; Duchonová, Radka (Circulation journal, 2007)
BACKGROUND: Implantation of a carotid artery stent after predilation is a standard approach in the endovascular treatment of carotid artery stenoses. Stenting without predilation may be an alternative approach in a certain subset of patients. The present prospective, single-center registry was designed to evaluate the feasibility and safety of direct carotid artery stenting (DCAS) in high-risk patients. METHODS AND RESULTS: Symptomatic patients with stenosis >50% and asymptomatic patients with stenosis >70% were eligible for enrolment. Criteria for high-risk patients included: need or history of open heart surgery, history of myocardial infarction, multivessel coronary artery disease, left ventricular dysfunction (ejection fraction < or =40%), severe pulmonary or renal disease, significant contralateral carotid disease, previous endarterectomy, and age > or =80 years. All procedures were performed using a filter protection device. Patients underwent complete clinical examination before and after DCAS and at 30-day follow-up. A total of 83 consecutive patients (45 males, 68+/-9 years, 33% symptomatic) underwent 100 procedures and 103 stents were deployed successfully. The technical success rate of stenting was 100%. Predilation of carotid stenosis was necessary in 1 (1%) procedure. Carotid-artery stenoses before and after DCAS were 80+/-9% and 7+/-9%, respectively. The median fluoroscopic time for DCAS was 7 min. The overall rate of in-hospital major adverse cerebrovascular events (death, stroke, myocardial infarction) was 5% (2 minor strokes, 3 transient attacks). There was 1 (1%) minor stroke within the 30-day follow-up. CONCLUSION: DCAS is feasible and can be performed with an acceptable risk in high-risk patients.
Keywords: Coronary Artery Disease; nemoci koronárních tepen; stenty; Cerebellum; Humans; lidé středního věku; nemoci ledvin; Stroke; Female; rizikové faktory; Aged; výsledek terapie; senioři; lidé; plicní nemoci; infarkt myokardu; cévní mozková příhoda; Stents; Carotid Stenosis; ženské pohlaví; Follow-Up Studies; Male; Lung Diseases; Middle Aged; Myocardial Infarction; Treatment Outcome; dysfunkce levé srdeční komory; Aged, 80 and over; stenóza arteria carotis; Ventricular Dysfunction, Left; mozeček; senioři nad 80 let; mužské pohlaví; prospektivní studie; Kidney Diseases; následné studie; Risk Factors; Prospective Studies